2009
DOI: 10.1002/fedr.200811105
|View full text |Cite
|
Sign up to set email alerts
|

Comparative leaf epidermis investigation in species of genus Crataegus L. (Rosaceae) from Bulgaria

Abstract: SummaryThe leaf epidermis structure of six Crataegus species from Bulgaria has been studied by light and scanning electron microscopy. Cyclocytic stomatal type, different types of simple single trichomes, cuticle ornamentation and waxes are determined. The results allow clear delimitation and identification of the species. Some conjectures about the relationships on inter-and intrageneric level and references of epidermal structure with adaptation to various ecological conditions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
3
13
0
2
Order By: Relevance
“…Comprehensive micromorphological studies of the genus Crataegus in Iran (Hamzehee et al unpubl.) as well as results of this paper, together with other previous treatments (Christensen and Hansen 1998, Ganeva et al 2009) show that micromorphological features are useful for the separation of Crataegus taxa.…”
Section: New Synonymsupporting
confidence: 78%
See 1 more Smart Citation
“…Comprehensive micromorphological studies of the genus Crataegus in Iran (Hamzehee et al unpubl.) as well as results of this paper, together with other previous treatments (Christensen and Hansen 1998, Ganeva et al 2009) show that micromorphological features are useful for the separation of Crataegus taxa.…”
Section: New Synonymsupporting
confidence: 78%
“…nov. and related species. Stomata number per 0.16 mm ² , size of stomata in μ m. Terminology generally followChristensen and Hansen (1998) andGaneva et al (2009).…”
mentioning
confidence: 86%
“…Molecular phylogenetic studies have suggested that epicuticular waxes could also include a phylogenetic signal (Heo et al 2013). The rodlet type of epicuticular wax with differences in diameter of the base was described for the first time for Maloideae (Ganeva et al ), although various types – granules, plates and platelets – have been reported for some species of the genera Crataegus (Ganeva et al ), Pyracantha , Mespilus , Cotoneaster (Uzunova and Mladenova ) and Malus (Ganeva and Uzunova ).…”
Section: Discussionmentioning
confidence: 99%
“…Characters of the leaf epidermis have proved useful for the classification and identification of difficult taxa such as Pinus (Whang et al 2001), basal angiosperms (Carpenter ), Salix (Chen et al , Ghahremaninejad et al ) and Scorzonera hispanica (Chwil et al 2015). Regarding Rosaceae, studies have been conducted on some genera: Rosa (Wissemann ), Cydonia (Ganeva ), Crataegus (Ganeva et al ), Malus (Ganeva and Uzunova ), Amelanchier (Ganeva and Uzunova ), Sibbaldia (Tahir and Rajput ) and Pyrus (Zamani et al 2017). Also in these genera have some such characters, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[19], Malus Mill. [20], Pyrus L. [18], Sorbus L. [18], Cydonia Mill. [21], Crataegus L. [22], Mespilus L. [17] and Pyracantha Roem.…”
Section: Discussionmentioning
confidence: 99%